Possibilities of improving paraxial brightness in rf ion sources - Mordyk, S.M.; Shulha, D.P.; Miroshnichenko, V.I.; Storizhko, V.E.; Voznyy, V.I. (Вопросы атомной науки и техники, 2005)
The paraxial brightness in rf ion sources can be improved by redistributing the beam phase density, increasing the beam current density and using beam extraction systems with low aberrations. Experimental data are presented for the central region of a hydrogen or helium ion beam extracted from a helicon rf ion source with permanent magnets. A high-voltage (~6 kV) extraction structure of the rf ion source was investigated with imposed external magnetic field. The evolution of phase sets in the extraction structure with emission hole size approaching Debye radius was calculated for the helium plasma density of ~10¹² cm⁻³ with imposed nonuniform external magnetic field. The calculations were performed involving data on ion energy spread (~25 eV) of the helicon rf ion source with permanent magnets.